2014
DOI: 10.1073/pnas.1412396111
|View full text |Cite
|
Sign up to set email alerts
|

Whole-cell, multicolor superresolution imaging using volumetric multifocus microscopy

Abstract: Single molecule-based superresolution imaging has become an essential tool in modern cell biology. Because of the limited depth of field of optical imaging systems, one of the major challenges in superresolution imaging resides in capturing the 3D nanoscale morphology of the whole cell. Despite many previous attempts to extend the application of photo-activated localization microscopy (PALM) and stochastic optical reconstruction microscopy (STORM) techniques into three dimensions, effective localization depths… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
102
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 102 publications
(102 citation statements)
references
References 35 publications
0
102
0
Order By: Relevance
“…While diffractive optics may incur some loss of photons, this approach has achieved up to ~84% diffraction efficiency for the case of nine planes ranging over 4 μm (113) and is compatible with single-molecule tracking(111) and super-resolution imaging with small molecules. (112) A drawback of multifocal methods that span a large axial range is inefficient use of signal, especially at the extremes of the focal stack, where much of the signal is split into planes that are too out of focus to provide useful information. To improve the 3D precision attainable from each plane, multifocal imaging has been combined with astigmatism (see section 3.2),(114, 115) and we anticipate the possibility of further interesting modifications to multifocus techniques.…”
Section: Methods For 3d Localizationmentioning
confidence: 99%
“…While diffractive optics may incur some loss of photons, this approach has achieved up to ~84% diffraction efficiency for the case of nine planes ranging over 4 μm (113) and is compatible with single-molecule tracking(111) and super-resolution imaging with small molecules. (112) A drawback of multifocal methods that span a large axial range is inefficient use of signal, especially at the extremes of the focal stack, where much of the signal is split into planes that are too out of focus to provide useful information. To improve the 3D precision attainable from each plane, multifocal imaging has been combined with astigmatism (see section 3.2),(114, 115) and we anticipate the possibility of further interesting modifications to multifocus techniques.…”
Section: Methods For 3d Localizationmentioning
confidence: 99%
“…For instance, in combination with PALM, simultaneous detection of each imaged focal plane and of a second plane that is 350 nm closer to the objective, improves the axial resolution to 75 nm (Juette et al, 2008). In addition, combination of multifocal excitation and localization microscopy has demonstrated the simultaneous imaging of a 4-µm volume within single cells with a resolution of 20×20×50 nm (Hajj et al, 2014). The main drawback of localization microscopy is that the subdiffraction resolution is achieved by localizing single fluorophores over time, which makes it less suitable for imaging fast dynamic processes.…”
Section: Localization Microscopymentioning
confidence: 99%
“…In this way, the authors demonstrated the parallel acquisition of a volumetric image with up to nine focal planes [126]. In a recent work, Hajj et al applied this technique to stochastic optical reconstruction microscopy (STORM) and demonstrated snapshot 3D superresolution imaging of a living cell [145]. In another follow-up work, Yu et al demonstrated that the number of depth layers for simultaneous imaging can be dramatically increased to ~50 by introducing Dammann phase-encoding into the original distorted grating [146].…”
Section: Snapshot Multidimensional Imaging Implementations and Appmentioning
confidence: 99%